DEVELOPMENT OF UIN AR-RANIRY CAMPUS INTRODUCTION MEDIA BASED ON 360-DEGREE VIDEO USING VIRTUAL REALITY - Maulana, Naufal; AR, Khairan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The purpose of this study is to replace the less effective method of drawing plan media as a campus introduction medium for visitors to UIN Ar-Raniry Banda Aceh. With digital technology increasingly developing, smartphone use can be directed to profitable activities, such as watching videos on YouTube. This 360-degree video was made to introduce the layout of the UIN Ar-Raniry campus building more interesting and interactive for visitors. This study uses research and development research methods and involves 50 visitors to the UIN Ar-Raniry campus as respondents. The results of the evaluation showed that 100% of media experts rated this 360-degree video as very feasible as a campus introduction medium, while visitor responses showed an average of 96% in the category of